Geology and Wine 1. Concept of Terroir and the Role of Geology - Haynes, Simon (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1999)
Summary Although Peigi Wallace presented apaper on the geology of wine at the 1972 International Geological Congress in Montreal, until recently there have been few publications on this topic. However, a remarkable book by J.E. Wilson appeared in 1998 on terroir and the role of geology, climate and culture in the making of French wines. Wilson emphasizes vineyard geology as a precursorto the soil, and the sub soil through which the grape vine grows, and that geology controls the topography and land form type present, thus influencing drainage and microclimate. This paper examines the ideas of Wilson and other authors on the concept of terroir, and discusses the key role of geology in wine grape regions.